Islamic Teachings on Working: Reflections of Surah Al-Qashash verse 73, Al-Jumu'ah verse 10, and Fathir verse 12 - Arlin Apriska Meisarah; Syuhud Syuhud (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2026)
This study aims to analyze the Islamic concept of work based on Surah Al-Qashash verse 73, Surah Al-Jumu'ah verse 10, and Surah Fathir verse 12. This research employs a qualitative method with a thematic interpretation approach and library research. Data were collected from the Qur'an, tafsir literature, books, and relevant scholarly articles. The findings reveal that work in Islam is considered both an act of worship and a responsibility of human beings as God's vicegerents on earth. These verses emphasize the importance of managing time effectively, earning lawful income, and utilizing natural resources responsibly. The values embedded in these teachings include sincerity, honesty, responsibility, professionalism, and balance between worldly and spiritual life. The implementation of these values can foster an Islamic work ethic that is productive and oriented toward divine blessings.